Avaliação do efeito da lectina de Cratylia floribunda em feridas cutâneas experimentais - Figueirêdo, Ingrid Samantha Tavares de (2008)
The tissue injury evokes a physiological process of complex cellular and biochemical events that results in wound healing. This process can be divided into three phases: inflammation, proliferation and remodeling. Lectins are (glyco)proteins that can recognize and reversibly bind to carbohydrates or other substances derived from sugars. Cratylia floribunda is a leguminous species, found only in South America, from which was isolated Cratylia floribunda lectin (CFL). The aim of this work was to evaluate the topical treatment of cutaneous wounds using CFL at a cicatricial model. Surgical wounds (1cm2) were produced aseptically in the dorsal region of male Swiss mice (27-33g; n=23/group), which were randomized in two experimental groups according to the treatment set: C (150 mM NaCl) or CFL (100 µg/mL). Wounds were treated topically, daily, with 100 µL from each solution throughout all the post-operative period (PO). Clinical evaluation of the skin lesions was performed along 12 days and the parameters investigated were some macroscopic signals of inflammation and fibroplasia. Cutaneous biopsies have been carried out at 2nd, 7th and 12th PO to histopathological analysis. In parallel, the ability of the lectin to induce the in vitro macrophage release of TNF-α, a pro-inflammatory cytokine, was evaluated. CFL reduced the frequency, intensity and duration of some flogistics signals, such as edema and hiperemy. At 10th and 11th PO the wounds treated with CFL had significantly less crust (p <0.05) than the lesions of the C group. CFL anticipated the formation of granulation tissue, being displayed in a greater percentage of skin lesions. The CFL group injuries presented a higher percentage of area contraction at the firsts day of treatment and this effect remained until the 12th PO (p<0,05). The major differences of the area contraction between the groups occurred at 1st PO (22.5%) and 5th PO (20.5%). CFL group showed a statistically lower area under the curve (AUC) of the area measures than the C group (C-6,27±0,85; CFL- 4,00±1,28, p<0.05). Compared to control group, CFL group showed a significant (p <0.05) percentual of animals with healed wounds at 10th and 11th PO. Treatment with the lectin anticipated the appearance of the cicatricial tissue, being statistically significant (p <0.05) the frequence that it was observed at 6th and 8th day PO. The histopathological analyses revealed that the treatment with CFL diminished the inflammatory phase of the wound healing. Moreover, the proliferation phase was anticipated in CFL group, since there was a fibrous granulation tissue since 7th PO on the lesions treated with CFL, while, at the same period in the C group lesions, there was an initial formation of the granulation tissue. At 12th PO, it was observed a complete reepithelization of the lesions treated with CFL, while, in C group lesions, there was a few collagen fibers among the granulation tissue. CFL stimulated the in vitro release of TNF-α in peritoneal macrophages culture of mice. Those results show that Cratylia floribunda lectin modulates the inflammatory phase of the cicatricial process from cutaneous lesions in mice. We postulate that in in vivo the lectin stimulates resident cells (macrophages) for liberation of TNF-α. Together, those results reveal that CFL favors the repair of lesions.